2021
DOI: 10.2176/nmc.oa.2020-0304
|View full text |Cite
|
Sign up to set email alerts
|

Nation-wide Brain Tumor Registry-based Study of Intracranial Meningioma in Japan: Analysis of Surgery-related Risks

Abstract: Although surgical resection is the most preferred treatment for intracranial meningiomas, a detailed analysis of the surgery-related risks based on large population data has not been conducted to date. In this study, we analyzed the nation-wide brain tumor registry to assess the surgical risk factors for intracranial meningiomas to provide information for an optimal treatment strategy. Data of 4081 meningioma patients who underwent initial resection between 2001 and 2008 were extracted from the Brain Tumor Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…This study showed a rate of overall major AE of 20.6% and a rate of 12.8% for onset of new focal neurological deficit, which are both in line with recently published studies in the literature [4,22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study showed a rate of overall major AE of 20.6% and a rate of 12.8% for onset of new focal neurological deficit, which are both in line with recently published studies in the literature [4,22].…”
Section: Discussionsupporting
confidence: 91%
“…Major AEs are common following meningioma surgery [ 4 , 22 ]. Many studies to-date have identified risk factors [ 3 , 7 , 11 , 16 , 17 , 20 , 24 , 31 ], but to our knowledge, none have looked specifically at major AE rates in first-time meningioma surgeries, including new focal neurological deficits as major AEs.…”
Section: Discussionmentioning
confidence: 99%
“…The JND was originally designed to have a multi-layered database, and the statistics of the first-layer database, covering all fields of subspecialties, is described in this paper. 1) Relevant societies of the subspecialties of the JNS published the paper using clinical registries such as the Japanese Registry of Neuroendovascular Therapy, 19 , 20 , 24) the Brain Tumor Registry of Japan, 25 , 26) the Japan Neurotrauma Data Bank, 6 , 27) and registries of pediatric neurosurgery, 28 , 29) functional neurosurgery, 30 , 31) unruptured aneurysms and cerebrovascular surgery, 32 , 33) moyamoya diseases, 34 36) and stereotactic radiosurgery.…”
Section: Discussionmentioning
confidence: 99%
“…Supratentorial NSBM account for 40 to 60% of all intracranial meningiomas [ 4 , 6 , 7 , 8 , 9 ] ( Table 1 ). Meningioma incidence increases with age, with a median age at diagnosis of 66 years [ 1 ].…”
Section: Epidemiologymentioning
confidence: 99%